OC-069 Mesalazine For Treatment Of Diarrhoea-predominant Irritable Bowel Syndrome (ibs-d): A Multi-centre, Parallel Group, Randomised Placebo Controlled Trial. (9th June 2014) - Lam, C; Tan, W; Leighton, M; Williams, J; Agrawal, A; Sen, S; Foley, S; Rutter, M; Ramadas, A; Whorwell, P; Montgomery, A; Spiller, R
Abstract : Introduction: "Immune activation" has been described in the mucosa of IBS-D patients which Mesalazine (M) could suppress. Our main aim was to compare the effect of M versus placebo (P) on stool frequency. Secondary endpoints were abdominal pain, stool consistency and satisfactory relief of IBS symptoms. Methods: All patients were required to have daily stool frequency of ≥3/day for more than 2 days/week for 2 weeks and stool consistency of ≥25% type 5–7 and ≤25% type 1–2 according to the Bristol Stool Form Scale. Subjects were randomised to either 2g M/ P for a week, to increase to 2 g twice/day for remaining 11 weeks if tolerated. All participants completed a 12-week stool diary. Since we expected M would require >2 months exert its effect, all primary and secondary outcomes were based on the stool diary completed during week 11–12. Satisfactory relief of IBS symptoms was defined as answering 'yes' to weeks 11 and 12 of the stool diary Results: 136 subjects with IBS-D, meeting the Rome III criteria, were randomised to the 2 groups. Mean (SD) age was 47.1 (13.5) years in P and 42.6 (15.2). Treatment compliance for P and M were similar, 59% and 58% respectively. Analysis by intention to treat showed M did not improve bowel frequency, abdominal pain and stool consistency compared to P during week 11–12. Treatment did not affect satisfactory relief of IBS symptoms, HAD, PHQ15 and EQ-5D VAS scores compared to P. See table below for results. Conclusion: This study did not show any clinically meaningful benefit or harm of M compared to P in this group of IBS-D patients. We need better phenotyping/ biomarkers for IBS patients to allow targeting of effective treatments. Disclosure of Interest: C. Lam: None Declared, W. Tan: None Declared, M. Leighton: None Declared, J. Williams: None Declared, A. Agrawal: None Declared, S. Sen: None Declared, S. Foley: None Declared, M. Rutter: None Declared, A. Ramadas: None Declared, P. Whorwell Grant/research support from: Danone, Almirall, Shire, Boehringer Ingelheim UK, Sucampo, Saliz, Chr-Hansen and Norgine, Consultant for: Danone, Almirall, Shire, Boehringer Ingelheim UK, Sucampo, Saliz, Chr-Hansen and Norgine, A. Montgomery: None Declared, R. Spiller Grant/research support from: Lessaffre, Ironwood, Consultant for: Almirall, Astellas, Danone and Sanofi, Conflict with: free drug for clinical trial from Norgine.